Peripheral Mechanisms of Symptom Generation in Irritable Bowel Syndrome - Stephen M Collins (Canadian Journal of Gastroenterology)
There is considerable interest in the mechanisms that underlie symptom generation in irritable bowel syndrome (IBS) and particularly those mechanisms peripheral to higher centres in the nervous system. While the central nervous system is important in IBS, it is restricted largely to the role of behaviour in stress perception and symptom reporting. The gut and the autonomic nervous system are principal areas of research in identifying mechanisms underlying symptom generation and in the identification of new targets for drug development. While motility changes occur in IBS, they are neither specific nor predictable, and this is one reason why drugs aimed at influencing motility patterns have enjoyed limited success to date. This success has prompted interest in sensory physiology to explain pain and other discomforts expressed by patients with IBS. Patients with IBS exhibit intolerance to rectal distension and other manoeuvres of the gut, while exhibiting normal or raised thresholds for somatic pain. The mechanisms underlying the development of hyperalgesia or allodynia in the gut remain to be determined. In other systems and experimental models, low grade inflammation is a predicable inducer of these states, and recent evidence suggests that a subpopulation of patients with IBS develop chronic symptoms after acute gastroenteritis. This and other inflammatory stimuli may induce a hyperalgesic state and alter motor function in patients with IBS. Substances that mediate these changes are not fully understood, but there is growing recognition of the role of serotonin as a sensitizing agent.